1241. Hepatitis C Cascade of Care in a Multidisciplinary Substance Use Bridge Clinic Model. (15th December 2022) - Simonyan, Ana; Chirunomula, Samantha; Whelchel, Kristen; Gispen, Fiona; Marcovitz, David; White, Katie D; Chastain, Cody A
Abstract: Background: Hepatitis C virus (HCV) infection is common among persons who inject drugs. Treating HCV in patients who present for treatment of substance use disorder (SUD) is an opportunity to improve linkage to and retention in care. The Vanderbilt University Medical Center (VUMC) Bridge Clinic serves a unique patient population that includes individuals with opioid use disorder who recently presented to VUMC for complications related to substance use. These patients are treated by a multidisciplinary team for addiction with opioid agonist therapy as well as comorbid medical conditions. The aim of this study is to further characterize the HCV cascade of care (CoC) in a bridge clinic setting and identify barriers to HCV treatment. Methods: We performed a single-center, ambispective cohort study of patients enrolled in the VUMC Bridge Clinic from 7/1/20 through 6/30/21. Data collection was continued through 12/31/21. All patients enrolled in the Bridge Clinic were reviewed, and patients with active HCV infection were monitored from initial evaluation through treatment and sustained virologic response (measured at least 12 weeks after completing therapy (SVR12). Descriptive statistics including demographics and progression through the CoC are presented. Results: Characteristics of the 230 patients screened for HCV are reflected in Table 1. The CoC is reflected in Figure 1. Of these 230 patients, 96 (42%) had detectable virus as measured by blood HCV RNA. Of these 96 patients, 39 (40%) were approved for treatment, 33 (34%) initiated treatment, 25 (26%) completed treatment, and 13 (14%) achieved SVR12 with laboratory confirmation. The largest number of patients who did not progress through the CoC were those not approved for treatment; the most common reasons were loss to follow-up or incomplete workup. The majority of patients received opioid agonist therapy as part of their multidisciplinary treatment plan. Conclusion: This study demonstrates opportunities and challenges for treating HCV in individuals with SUD in a bridge clinic model. Ongoing efforts should focus on linkage to care and strategies to keep individuals with SUD engaged throughout HCV treatment. Disclosures: David Marcovitz, MD, Better Life Partners LLC: Stocks/Bonds|Silver Pines LLC: Stocks/Bonds.